Does Continuity of The Body Determine Personal Identity? - Andrade, Gabriel (Revista de Filosofía, 2020)
Philosophers have long asked a fundamental metaphysical question: by what criterion can a person persist in her identity? The most common-sense criterion is the body, according to which, a person persists in her identity, if and only if the same body is preserved. Despite its intuitive appeal, this position brings forth many interesting philosophical questions. Some interesting thought experiments, such as the ship of Theseus, can shed light on the adequateness of the body criterion. Yet, other thought experiments, mostly derived from Derek Parfit’s philosophy, invite further thought about the adequateness of the body as criterion for personal identity. This article examines these questions.